2020
DOI: 10.1016/j.envdev.2020.100555
|View full text |Cite
|
Sign up to set email alerts
|

The living marine resources in the Mediterranean Sea Large Marine Ecosystem

Abstract: The Mediterranean Large Marine Ecosystem (Med-LME) is a heterogeneous system that, despite its oligotrophic nature, has high diversity of marine species and high rate of endemism, making it one of the world hotspots for marine biodiversity. The basin is also among the most impacted Large Marine Ecosystems in the world due to the combined multiple stressors, such as fishing pressure, habitat loss and degradation, climate change, pollution, eutrophication and the introduction of invasive species. The complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…Simulating their dynamics under different scenarios, depleted stocks would decrease to just 46% in 2030 with 0.95 fishing mortality at MSY (F MSY ), while this percentage decreases to 6% with more drastic reduction of fishing effort (no fishing takes place when the stock is depleted and fishing occurs with 0.5 F MSY when biomass is equal to or larger than half the B MSY ). A current fishing pressure exceeding several times the MSY was more recently confirmed by Hilborn et al (2020) and Piroddi et al (2020). In the last years, however, there has been a decrease in the percentage of stocks in overfishing (from 88% in 2012 to 75% in 2018), as well as in the average exploitation ratio (F/F MSY ), which has decreased from 2.9 to 2.4 times the F MSY over the same period (Food and Agriculture Organization (FAO), 2020).…”
Section: The Status Of the Main Demersal And Small Pelagic Stocksmentioning
confidence: 84%
See 1 more Smart Citation
“…Simulating their dynamics under different scenarios, depleted stocks would decrease to just 46% in 2030 with 0.95 fishing mortality at MSY (F MSY ), while this percentage decreases to 6% with more drastic reduction of fishing effort (no fishing takes place when the stock is depleted and fishing occurs with 0.5 F MSY when biomass is equal to or larger than half the B MSY ). A current fishing pressure exceeding several times the MSY was more recently confirmed by Hilborn et al (2020) and Piroddi et al (2020). In the last years, however, there has been a decrease in the percentage of stocks in overfishing (from 88% in 2012 to 75% in 2018), as well as in the average exploitation ratio (F/F MSY ), which has decreased from 2.9 to 2.4 times the F MSY over the same period (Food and Agriculture Organization (FAO), 2020).…”
Section: The Status Of the Main Demersal And Small Pelagic Stocksmentioning
confidence: 84%
“…Although a situation of overfishing is clearly outlined both for demersals and small pelagics, available information on biomass at sea seems to depict signs of a recovering process. Coupling food web modeling with a hydrodynamical-biogeochemical model (Piroddi et al, 2020) has found increases in the biomass level of elasmobranchs, large pelagics, small and medium demersals, and meso-and bathypelagic fishes when comparing the middle of the 2010s to the late 1990s. Conversely, decreases of large demersal fishes, small pelagics, and commercial and non-commercial cephalopods and crustaceans were reported.…”
Section: The Status Of the Main Demersal And Small Pelagic Stocksmentioning
confidence: 99%
“…Further studies should better evaluate this aspect when/if more data (in open waters) become available. The use of spatially explicit environmental variables from hydrodynamic-biogeochemical models, extracted as in this case at different depths, highlighted the importance of considering such tools to better capture fish dynamics and their linkage with the environment (Piroddi et al, 2017(Piroddi et al, , 2020.…”
Section: Estimates Of Biomassmentioning
confidence: 99%
“…The Mediterranean Sea is also defined a sea "under siege" because the basin accumulates the impact of multiple stressors, such as fishing, climate change, invasive species, and pollution, on its ecosystem (Coll et al, 2010;Katsanevakis et al, 2014). Several regional studies, in fact, have reported severe declines of predatory species in the region (Ferretti et al, 2008;Piroddi et al, 2017Piroddi et al, , 2020 with important consequences to its biodiversity. Thus, assessing how many mesopelagic fish inhabit the basin and where they distribute is a step further in understanding the role of mesopelagic fish in the functioning and structuring of this fragile ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we applied the new developments of the EwE modelling approach to first quantify and analyse in space and time (1995–2016) past ecosystem dynamics using a set of ecological indicators and then evaluate spatial–temporal historical (1995–2016) responses of these indices to changes in environmental factors and fisheries in the Mediterranean Sea. This basin is a hotspot of marine diversity 27 and yet it is one of the Large Marine Ecosystems in the world that is most threatened by multiple anthropogenic pressures 28 , 29 , with severe signs of degradations at species-, community- and ecosystem levels 27 , 30 . The spatial–temporal analyses planned in this study aim at identifying areas and ecosystem components that show signs of deterioration, with the overarching goal to identify past trajectories and support future marine policy actions in the region.…”
Section: Introductionmentioning
confidence: 99%